PERAN UMKM DALAM PEMBANGUNAN DAN KESEJAHTERAAN MASYARAKAT KABUPATEN BLORA - Adnan Husada Putra (Jurnal Analisa Sosiologi, 2016)
According data from the Ministry of Cooperatives and Small and Medium Enterprises in 2014, there are about 57.8 million actors of MSMEs in Indonesia. In 2017 and the next few years it is estimated that the number of MSME perpetrators will continue to grow. MSMEs have an important and strategic role in national economic development. In addition to its role in economic growth and employment, MSMEs also play a role in distributing development outcomes. So far, MSME has contributed 57,60% Gross Domestic Product (PBD) and employment rate about 97% of all national work force (MSME Business Profile by LPPI and BI 2015). SMEs have also been proven not affected by the crisis. When the crisis hit the period of 1997-1998, only MSMEs were able to remain strong. Data from the Central Bureau of Statistics shows that after the economic crisis of 1997-1998 the number of MSMEs has not decreased, it has been increasing, even absorbing 85 million to 107 million workers until 2012. In that year, the number of entrepreneurs in Indonesia is 56,539,560 units. Of this amount, Micro Small and Medium Enterprises (MSMEs) of 56,534,592 units or 99.99%. The rest, about 0.01% or 4,968 units is a major undertaking. Examples of MSME policies of Blora district government regarding the role of MSMEs in development, especially in Blora district itself. Government at the central, provincial, to district / municipal levels are required to improve the welfare of their citizens through various efforts and innovation. To be able to achieve these goals, there are stages and processes that must be passed. So it takes seriousness with all related parties and inter-regional cooperation ties. Application of populist economy in order to realize the development and welfare of the community. The real form of the populist economy is in the form of support to micro, small and medium enterprises (MSME), so that the production of MSMEs is not only marketed in the local market but also outside the region and growing. Moreover, if supported by the use of information technology, product marketing is no longer limited by time and place.Keywords: MSME (Micro, Small, Medium Enterprise), Development, Community Welfare.AbstrakBerdasarkan data dari Kemenrian Koperasi dan UMKM pada tahun 2014, terdapat sekitar 57,8 juta pelaku UMKM di Indonesia pada tahun 2017 dan beberapa tahun kedepan diperkirakan bahwa jumlah pelaku UMKM akan terus bertambah. UMKM memiliki peran penting dan strategis dalam perkembangan ekonomi nasional. Sebagai tambahan dalam perannya dalam perkembangan ekonomi dan ketengakerjaan, UMKM juga berperan dalam perkembangan distribusi hasil. Sejauh ini, UMKM telah berkontribusi sebanyak 57,60% Produk Domestik Bruto (PBD) dan mempunyai tingkat penyerapan tenaga kerja sekitar 97% dari seluruh tenaga kerja nasional (Profil Bisnis UMKM oleh LPPI dan BI, 2015). UKM juga telah terbukti tidak terpengaruh oleh krisis. Ketika krisis yang melanda pada periode 1997-1998, hanya UMKM yang dapat kuat bertahan. Data dari Badan Pusat Statistik menunjukan bahwa setelah krisis ekonomi 1997-1998 jumlah UMKM tidak berkurang, UMKM bertambah, bahkan menyerap 85 juta hingga 107 juta pekerja hingga tahun 2012. Pada tahun itu, jumlah pengusaha di Indonesia sebanyak 56,539,560 unit. Dari jumlah ini, UMKM menduduki jumlah 56,534,592 unit atau sebanyak 99,99%, selebihnya sekitar 0,01% atau 4.968 unit adalah pengusaha besar. Contoh dari kebijakan UMKM di pemerintahan kabupaten Blora terkair dengan peran dari UMKM terhadap pembangunan, secara khususnya di Kabupaten Blora sendiri. Pemerintah pusat, provinsi hingga tingkat kabupaten/kotamadya diperlukan peningkatan kesejahteraan masyarakat melalui berbagai usaha dan inovasi. Untuk dapat mencapai tujuan tersebut, terdapat beberapa langkah dan proses yang harus dilewati. Sehingga dibutuhkan keseriusan seluruh pihak yang terkait dan ikatan kerjasama antar daerah. Aplikasi populisme ekonomi dalam upaya untuk merealisasikan pembangunan dan kesejahteraan dari masyarakat. Bentuk nyata dari populisme ekonomi adalah dalam bentuk dukungan kepada UMKM, sehingga produksi UMKM tidak hanya dipasarkan di pasar lokal namun juga merambah ke pasar yang lebih luas. Selain itu, jika didukung oleh penggunakan informasi teknologi, pemasaran produk tidak lagi terhambat oleh waktu dan tempat.Kata Kunci: Usaha Mikro Kecil Menengah Pembangunan, Kesejahteraan Masyarakat.